SINS model in the management of biosafety level 2 laboratories: exploration and practice - Xiaoxia Qiu; Jingqing Weng; Zhenggang Jiang; Congcong Yan; Hua Gu (Elsevier, 2019)
A significant number of biosafety level 2 (BSL-2) laboratories have been established in many countries for studies of various types of pathogenic agents and other infectious biological materials. The harmonized management of biological risks in such diverse laboratories thus appears as a real challenge. Zhejiang Province in China has taken the initiative to establish a comprehensively integrated laboratory biosafety management system called SINS (Standardization, Informatization, Normalization and Systematization). The SINS model system has been introduced and adopted in 1,721 BSL-2 laboratories in Zhejiang Province, and thus lead to an increase in the number of biosafety committees from 20% to more than 95% from 2007 to 2018, and the number of biosafety laboratory managers who knows biosafety-related laws and regulations increase from 52.7% to 83.7% from 2009 to 2017. Such achievements indicate that the successful implementation of SINS model has increased the effective control of biological risks in BSL-2 laboratories of the Zhejiang Province. SINS model and its main effects on leading the improvement of laboratory biosafety management was presented in this review. The SINS model helps to strengthen laboratory biosafety and thus effectively reduces occurrence of biosafety-related incidences. This model can potentially be used by other regions or countries where harmonized biosafety management system is still under-developing.